Perlindungan Hukum Terhadap Korban Tindak Pidana Terorisme; Korelasi Hukum Pidana Islam dan Hukum Positif - Butar Butar, M. Ridho; Azizah, Noor (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2024)
Legal protection for victims of terrorism should ensure justice and welfare for the victims, both from the perspective of Islamic criminal law and positive law. In reality, the application of law in Indonesia, particularly in the context of victim protection from terrorism, still faces challenges such as legal obstacles and limitations in victim protection mechanisms. This research aims to examine legal protection for terrorism victims from the perspectives of both Islamic criminal law and positive law. This article falls under qualitative legal research. The methodology employed is a normative juridical study with a correlational analysis between Islamic law and positive law. The findings conclude that legal protection for terrorism victims in the context of Islamic criminal law and positive law aims to protect victims' rights and ensure justice. Islamic criminal law emphasizes victim restitution through diyat (compensation) and qisas (retributive justice), while positive law in Indonesia focuses on restitution and state compensation. Despite their different approaches, both are complementary in ensuring victim protection.